‘El trabajo dignifica’ Twentieth Century Afro-Costa Rican Women and Informal Work in Port Limon, Costa Rica - Hutchinson Miller, Carmen (2019)
The patriarchal system has convinced most that women’s respectable place and function are exclusively within the private space of the home. When women ‘transgress’ and venture out into the public sphere by choice or by force, the reception is far from welcoming both by individuals and institutions. The analysis seeks to enquire, based on women of African descent history, how this ideology affects their participation in the public sphere. The main objective is to unearth and make visible some of the informal financial activities women were involved in during the 20th century in Port of Limon, Central America, Costa Rica. The information was gathered through interviews, some early 20th-century newspaper research, and other documentation. The analysis is conducted from a historical and gender perspective.